A Multidisciplinary Hypothesis about Serotonergic Psychedelics. Is it Possible that a Portion of Brain Serotonin Comes From the Gut? - Császár-Nagy, Noémi; Bob, Petr; Bókkon, István (Journal of integrative neuroscience, 2022)
Here we present a complex hypothesis about the psychosomatic mechanism of serotonergic psychedelics. Serotonergic psychedelics affect gut microbes that produce a temporary increase of 5-HT by their host enterochromaffin cells (ECs). This increased 5-HT production-which is taken up and distributed by platelets-may work as a hormone-like regulatory signal that could influence membrane permeability in the host organs and tissues and in the brain. Increased plasma 5-HT levels could enhance permeability of the blood-brain barrier (BBB). Transiently increased permeability of the BBB allows for plasma 5-HT to enter the central nervous system (CNS) and be distributed by the volume transmission. Next, this gut-derived 5-HT could modulate excitatory and inhibitory neurotransmission and produce special network disintegration in the CNS. This transient perturbation of the normal neural hierarchy allows patients access to suppressed fear information and perform an emotional reset, in which the amygdale may have a key role.
Keywords: hematoencefalická bariéra; Serotonin; classic psychedelics; platelets; halucinogeny; lidé; hormony; serotonin; Hallucinogens; Hormones; membrane permeability; gut-brain axis; amygdala; Brain; volume transmission; Blood-Brain Barrier; mozek; Humans